2017
DOI: 10.3390/ma10121358
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clinically Relevant CAD/CAM Zirconia Polishing on Gingival Fibroblast Proliferation and Focal Adhesions

Abstract: Mucosal seal formation around dental abutments is critical to the successful integration of dental implants into the human oral cavity. No information exists for how clinically relevant polishing procedures for computer-aided design and computer-aided manufactured (CAD/CAM) zirconia abutments affects cellular responses important to mucosal seal formation. CAD/CAM zirconia was divided into four groups for clinically relevant polishing utilizing commercial polishing heads: control, coarse, coarse plus medium, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 75 publications
2
21
0
1
Order By: Relevance
“…Cells grown on a rough surface stabilize themselves on topographic irregularities, not needing to develop a strong cytoskeleton. Fibroblasts grown on smoother surfaces in order to mechanically stabilize develop a strong network of actin fibers, appearing more elongated and spread [ 40 , 42 , 43 ]. This explains why the fibroblasts grown on Y-TZP showed a greater extension of the actin filaments and an elongated shape.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cells grown on a rough surface stabilize themselves on topographic irregularities, not needing to develop a strong cytoskeleton. Fibroblasts grown on smoother surfaces in order to mechanically stabilize develop a strong network of actin fibers, appearing more elongated and spread [ 40 , 42 , 43 ]. This explains why the fibroblasts grown on Y-TZP showed a greater extension of the actin filaments and an elongated shape.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus about which is the best surface to create a good mucosal seal and reduce bacterial adhesion. Some authors have reported the importance of this surface being smooth [ 8 , 11 , 39 , 42 ], while other authors have shown that rough surfaces are preferred, either through some surface treatment like sandblasting—with random cell growth—[ 7 , 45 ], or the creation of micro-roughness [ 5 ] to enhance attachment, proliferation, and spreading in the direction of the microgrooves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, the effect of solid-state lasers on temperature rise and mechanical properties was analysed in the current research. Furthermore, we also adopted a novel approach as a standardised method for curing of dental restorative composites using CAD (computer-aided design)/CAM (computer-aided manufacturing) systems [ 32 , 33 , 34 ] equipped with LCUs.…”
Section: Introductionmentioning
confidence: 99%